Spectrum of primary salivary gland tumors with special emphasis on their management and outcome at a rural tertiary care centre - Samaddar, Dwaipayan; Samaddar, Jaya B.; Aziz, Ahmad M. (International Surgery Journal, 2020)
Background: Salivary gland tumors (SGT) are uncommon tumors of diverse histopathology accounting for <2% of all neoplasms. Early diagnosis differentiates between benign and malignant SGT and less extensive surgical procedure can be performed. The objective is to study the spectrum of primary SGT with special emphasis on their distribution, treatment and outcome at a rural tertiary care centre. Methods: A prospective observational study was conducted on 30 consecutive primary SGT patients attending the Departments of Surgery and Otorhinolaryngology of North Bengal Medical College and Hospital over a period of one and half years. All patients were clinically evaluated, investigated, treated accordingly and followed up during the period of study. Data was collected and compiled in Excel sheet and analysed using GraphPad Software and GraphPad QuickCalcs 2018 (San Diego, CA). A p value <0.05 was considered statistically significant. Results: Maximum patients (83.3%) were in the age range of 31-60 years. The male to female ratio was 1:4 for benign tumours and 1:1 for malignant tumours. Malignant cases were 66.67%. Involvement of parotid gland was the commonest (43.3%) and mostly presented with swelling (73.3%). Pleomorphic salivary adenoma was the commonest benign tumor (33.3%) and mucoepidermoid carcinoma was the commonest malignant tumor (16.7%). Permanent facial palsy was observed in 2 (9.5%) and recurrence in 4 patients (19%). Conclusions: SGT are rare and present in various modes. Malignant cases were singularly more in this study.